2018
DOI: 10.1063/1.5042346
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review Article: Multi-tip scanning tunneling microscopy: Experimental techniques and data analysis

Abstract: In scanning tunneling microscopy, we witness in recent years a paradigm shift from "just imaging" to detailed spectroscopic measurements at the nanoscale and multi-tip scanning tunneling microscope (STM) is a technique following this trend. It is capable of performing nanoscale charge transport measurements like a "multimeter at the nanoscale." Distance-dependent four-point measurements, the acquisition of nanoscale potential maps at current carrying nanostructures and surfaces, as well as the acquisition of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 87 publications
(104 reference statements)
0
51
0
Order By: Relevance
“…Conceptual sketch of the electrical measurement setup and the resulting potential along the line of the linearly arranged STM tips. While a NM voltage probe senses the local spin-averaged potential indicated by the black line (that is logarithmically-shaped in case of a two-dimensional infinite plane 31 ), a magnetised FM tip acquires the spin-chemical potential V s . As the spin voltage scales with the current density according to Eq.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Conceptual sketch of the electrical measurement setup and the resulting potential along the line of the linearly arranged STM tips. While a NM voltage probe senses the local spin-averaged potential indicated by the black line (that is logarithmically-shaped in case of a two-dimensional infinite plane 31 ), a magnetised FM tip acquires the spin-chemical potential V s . As the spin voltage scales with the current density according to Eq.…”
Section: Figurementioning
confidence: 99%
“…To magnetise the nickel tip in-situ, we use an electromagnet inside the STM chamber. With only one of the two voltage probes being sensitive to the spin orientation of charge carriers, the measured voltage difference between the two comprises an ohmic component V Ω and a spin-dependent component V s , as for purely two-dimensional charge transport 31 . The corresponding distances are depicted in Fig.…”
Section: Figurementioning
confidence: 99%
“…Analogous to the role of local temperature in thermal transport at the nanoscale, the knowledge of local electrochemical potential is not only important as a source of information about electrical properties of a nanosystem, but also is of fundamental importance to understand and explore charge transport at the nanoscale [452][453][454]. In practice, a local electrochemical potential of electrons can be measured by a scanning tunneling potentiometry with the spatial resolution down to several nanometers [455][456][457][458].…”
Section: Local Electrochemical Potential Of Two-dimensional Networkmentioning
confidence: 99%
“…Four-tip STM measurements in UHV ( Fig. 8(a)) [138], however, revealed that the resistance as a function of distance between the tips is not described by a 3D transport model only, but required a sizable contribution from a parallel 2D transport channel ( Fig. 8(b)−(c)).…”
Section: Edge States Of Weak Topological Insulatorsmentioning
confidence: 99%
“…With four-tip STM, two tips can be used to inject the current, while a third tip is scanned in between to probe the nullifying voltage [138,142]. Consequently, the current induced potential is mapped.…”
Section: Edge States Of Weak Topological Insulatorsmentioning
confidence: 99%